Solitary fibrous tumor mimicking adrenal tumor concomitant with contralateral adrenal pheochromocytoma: A case report of surgical resection after long-term observation - Kuribayashi, Sohei (Int J Surg Case Rep, 2019)
INTRODUCTION: Solitary fibrous tumors (SFT) usually originate from the pleura and rarely occur in the retroperitoneum. There were few reports of SFT around the adrenal gland and its long-term clinical behavior remains unknown. PRESENTATION OF CASE: A 62-year-old woman with bilateral adrenal tumors was referred to our department in 2008. She had elevated urinary normetanephrine. Metaiodobenzylguanidine scintigraphy showed uptake in the right adrenal gland. The tumor in the right adrenal gland was 5 cm in diameter. The patient underwent right adrenalectomy and was diagnosed with pheochromocytoma. The left tumor was 3 cm in diameter and diagnosed as benign using imaging. However, its size gradually increased to 10 cm over 7 years after surgery. The catecholamine hormones were within normal range. The patient underwent the tumor resection and left partial adrenalectomy. A steroid cover was given temporarily after surgery for prophylactic purposes. The histological diagnosis was solitary fibrous tumor. There was no recurrence 2 years after surgery. DISCUSSION: There have been only nine case reports of SFTs that were diagnosed as adrenal tumor by clinical imaging in the English literature. Total adrenalectomy was performed in all patients with a unilateral tumor. One patient with bilateral tumors underwent partial adrenalectomy. CONCLUSION: SFT in the periadrenal region is difficult to differentiate from adrenal tumor. However, tumor resection with partial adrenalectomy should be considered for enlarged tumor with less aggressive behavior in patients with a history of contralateral adrenalectomy.